2011
DOI: 10.1074/jbc.m110.217638
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Processing of Angiopoietin-like Protein 4 by Proprotein Convertases Modulates Its Inhibitory Effects on Lipoprotein Lipase Activity

Abstract: Angiopoietin-like protein 4 (ANGPTL4) has been associated with a variety of diseases. It is known as an endogenous inhibitor of lipoprotein lipase (LPL), and it modulates lipid deposition and energy homeostasis. ANGPTL4 is cleaved by unidentified protease(s), and the biological importance of this cleavage event is not fully understood with respect to its inhibitory effect on LPL activity. Here, we show that ANGPTL4 appears on the cell surface as the full-length form, where it can be released by heparin treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
101
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 31 publications
6
101
0
Order By: Relevance
“…In agreement with what has been reported previously (36,37), the N-terminal portion of ANGPTL4 was a more potent inactivator of LPL than full-length ANGPTL4 (Fig. 9B).…”
Section: Relative Effects Of Full-length Angptl4 and Its N-terminalsupporting
confidence: 81%
“…In agreement with what has been reported previously (36,37), the N-terminal portion of ANGPTL4 was a more potent inactivator of LPL than full-length ANGPTL4 (Fig. 9B).…”
Section: Relative Effects Of Full-length Angptl4 and Its N-terminalsupporting
confidence: 81%
“…Like EL, ANGPTL 3 and 4, which have a consensus PC recognition site, can inhibit LPL activity by enhancing its cleavage. Lei et al [17] found that cleaved ANGPTL4 can be detected in furindeficient cells, and furin overexpression only had moderate effects on ANGPTL 4 cleavage, suggesting that furin is not the only PC that cleaves ANGPTL4. They identified that several PCs, including furin, PC5/6 and PACE4 but not PCSK9, are responsible for ANGPTL4 cleavage, resulting in the production of the N-terminus of ANGPTL4, a more potent LPL inhibitor.…”
Section: Etiologicalmentioning
confidence: 99%
“…The N-terminal domain is a coiled-coil that mediates oligomerization of the protein, and the C-terminal portion is a fibrinogen-like domain (18). After ANGPTL4 is secreted, these domains are cleaved apart by the action of pro-protein convertases (18,19). The N-terminal domain inhibits LPL activity, and cleavage of the two domains enhances this inhibition (18,20,21).…”
Section: Lplmentioning
confidence: 99%